Effect of the rally length on performance according to the final action and the playing level in high-level men`s volleyball - Sánchez-Moreno, J.; Mesquita, I.; Afonso, J.; Millán-Sánchez, A.; Ureña, A. (Revista Internacional de Ciencias del Deporte, 2018)
The aim of this study was to analyze how rally length affected performance according to the final action of the rally and the playing level, as well as to identify potential critical rallies associated with rally length in high-level men`s volleyball. Thirty-one matches (5,438 rallies) of the top ranking national teams were sampled from two of the premier worldwide competitions: Men`s World Championship and Men`s World League. Rallies between eight and ten seconds emerged as critical incidents of the game, changing the general trend in performance according to the final action of the rally (attack point or attack error with or without opposite team`s contact). Rallies longer than ten seconds seemed to balance the chances of success between both teams, with the team in the side-out phase losing the initial advantage of being the first team to attack. Differences were found among teams of similar level, suggesting that the ability to efficiently manage some game situations might be attributed to team`s features. Coaches may deliver drills with varying playing styles and strategies depending on the length of the really, determining the degree of risk according to the length.